Civic Hope and the Perceived Authenticity of Democratic Participation. Issue 4 (May 2023) - Maffly-Kipp, Joseph; Holte, Patricia N.; Stichter, Matt; Hicks, Joshua A.; Schlegel, Rebecca J.; Vess, Matthew
In two studies, we tested how the expression of civic hope in narratives and the perceived authenticity of civic/political actions relate to civic/political engagement. In a cross-sectional study of undergraduates ( N = 230), the expression of civic hope predicted the perceived authenticity of civic actions (e.g., voting), which in turn predicted the motivation to engage in them. In a longitudinal on-line study that began 8 weeks prior to the 2020 U.S. Presidential election ( N = 308 MTurk workers), overall expressions of civic hope positively predicted the perceived authenticity of voting and the motivation to vote. In addition, expressions of civic hope positively predicted the perceived authenticity of voting, which in turn positively predicted the likelihood of reporting that one did vote. These findings indicate that a sense of civic hope and the experience of authenticity in political contexts may be important for democratic engagement.